1997
DOI: 10.1076/ejom.35.2.105.13068
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Distribution of NADPH-Diaphorase-Positive Neurons in the Cat?s Claustrum

Abstract: The NADPH-diaphorase histochemical technique was used to visualize the morphological features of the NADPH-diaphorase positive cells and fibres, and their distribution in both parts of the cat's claustrum. Taking into account the size and form of the perikaryon and the dendritic and axonal characteristics, the neurons are grouped in different subclasses: large, medium-sized and small. The present data suggest the occurrence of two populations of NADPH-diaphorase neurons in the claustrum. One population consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…Our present data are in a good agreement with our previous works (Hinova-Palova et al 1997) where the throughout distribution of NADPHd positive neurons in the DC of cat was reported. In spite of the good correlation between both NADPHd staining and nNOS-ir (Dawson et al 1991b;Hope et al 1991;Lysakowski and Singer 2000), some remarks must be made: First, the NADPHd staining results in significant background staining and it reveals more neuronal processes with axonal appearance.…”
Section: Discussionsupporting
confidence: 96%
See 2 more Smart Citations
“…Our present data are in a good agreement with our previous works (Hinova-Palova et al 1997) where the throughout distribution of NADPHd positive neurons in the DC of cat was reported. In spite of the good correlation between both NADPHd staining and nNOS-ir (Dawson et al 1991b;Hope et al 1991;Lysakowski and Singer 2000), some remarks must be made: First, the NADPHd staining results in significant background staining and it reveals more neuronal processes with axonal appearance.…”
Section: Discussionsupporting
confidence: 96%
“…In fact according to the best of our knowledge there is a single work describing the nNOS-ir in the DC of a cat (Rahman and Baizer 2007). In one of our previous works we reported the morphology and distribution of NADPH diaphorase (NADPHd) positive neurons in DC of a cat (Hinova-Palova et al 1997). Some of present data were already reported (Hinova-Palova et al 2005).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Hinova-Palova et al showed that there are two populations of NADPH-dr neurons in the CL. One population, consisting of large and medium-sized positive neurons, represents projection neurons, while the other population of small positive neurons corresponds to local circuit neurons [13] and only the densely stained cells were GABA immunoreactive [11]. In our experiments, it was found that a large number of NADPH-dr neurons are localized in Pu, especially in the ventral part.…”
Section: Discussionsupporting
confidence: 46%
“…The insular claustrum and endopiriform nucleus contain populations of projection neurons with polymorphous perikarya and spiny dendrites [Brand, 1981;LeVay and Sherk, 1981] some of which may be NADPH-diaphorase positive [Hinova-Palova et al, 1997], as well as interneurons [Braak and Braak, 1982] which are immunoreactive for calcium binding proteins [Druga et al, 1993;Kowianski et al, 2004] and are characterized by round or ovoid perikarya and aspinous, beaded dendrites [Reynhout and Baizer, 1999]. In some species complementarity of immunoreactivity for parvalbumin (Pv) and calretinin (Cr) has been observed in the insular claustrum, with a strongly Pv immunoreactive region corresponding in position within the insular claustrum to a Cr immunonegative region [Druga et al, 1993;Paxinos et al, 1999;Real et al, 2003].…”
Section: Introductionmentioning
confidence: 99%